Orange G and Remazol Brilliant Blue R decolorization by white rot fungi Dichomitus squalens, Ischnoderma resinosum and Pleurotus calyptratus - Eichlerová, Ivana; Homolka, Ladislav; Lisá, Ludmila; Nerud, Frantisek (Chemosphere, 2005)
Thirty different white rot strains were screened for Orange G and Remazol Brilliant Blue R (RBBR) decolorization on agar plates. Three promising strains, Dichomitus squalens, Ischnoderma resinosum and Pleurotus calyptratus, selected on the basis of this screening, were used for decolorization study in liquid media. All three strains efficiently decolorized both Orange G and RBBR, but they differed in decolorization capacity depending on cultivation conditions and ligninolytic enzyme production. Two different decolorization patterns were found in these strains: Orange G decolorization in I. resinosum and P. calyptratus was caused mainly by laccase, while RBBR decolorization was effected by manganese peroxidase (MnP); in D. squalens laccase and MnP cooperated in the decolorization processes.
Keywords: chemické látky znečišťující vodu; Azo Compounds; Laccase; Water Pollutants, Chemical; azosloučeniny; Coloring Agents; lakasa; Anthraquinones; Water Purification; Basidiomycota; anthrachinony; čištění vody; Biodegradation, Environmental; biodegradace; barvicí látky